ASSOCIATION OF ENAM C2452T POLYMORPHISM WITH HIGH RATES OF CARIES OCCURRENCE IN AN INDONESIAN POPULATION - NICOLINE, NICOLINE; PARTAKUSUMA, FATIMAH BOENJAMIN; JOENOES, HEDIJANTI; TALBOT, CHRISTOPHER; AUERKARI, ELZA IBRAHIM (International Journal of Applied Pharmaceutics, 2020)
Objective: Tooth decay or the caries process is a common dental problem that affects millions of people worldwide. Many risk factors are modifiable, while others are not (e.g., genetic factors). Polymorphism of the enamelin (ENAM) gene, which is required to ensure production of an essential protein for enamel development, may pose as a risk factor for the caries process. This study sought to investigate the possibility of ENAM C2452T polymorphism acting as a risk factor in the caries process. Methods: The polymerase chain reaction–restriction fragment length polymorphism method was employed to evaluate DNA samples taken from 95 subjects with a high caries prevalence and 89 control subjects for ENAM C2452T polymorphism. Results: Based on Chi-squared tests, there were significant genotype and allele distribution differences between the group with a high caries prevalence and the control group (p=0.005 and p=0.007). Polymorphism in this context may, therefore, serve as a risk factor for caries onset and progression (OR: 3.62). Conclusion: ENAM C2452T polymorphism is related to the caries process and may constitute a risk factor.